Sarm1 deficiency impairs synaptic function and leads to behavioral deficits, which can be ameliorated by an mGluR allosteric modulator - Lin, Chia-Wen; Chen, Chiung-Ya; Cheng, Sin-Jhong; Hu, Hsiao-Tang; Hsueh, Yi-Ping (Frontiers in Cellular Neuroscience, 2014)
Innate immune responses have been shown to influence brain development and function. Dysregulation of innate immunity is significantly associated with psychiatric disorders such as autism spectrum disorders (ASD) and schizophrenia, which are well-known neurodevelopmental disorders. Recent studies have revealed that critical players of the innate immune response are expressed in neuronal tissues and regulate neuronal function and activity. For example, Sarm1, a negative regulator that acts downstream of TLR3 and TLR4, is predominantly expressed in neurons. We have previously shown that Sarm1 regulates neuronal morphogenesis and the expression of inflammatory cytokines in the brain, which then affects learning ability, cognitive flexibility and social interaction. Because impaired neuronal morphogenesis and dysregulation of cytokine expression may disrupt neuronal activity, we investigated whether Sarm1 knockdown affects the synaptic responses of neurons. We show that reduced Sarm1 expression impairs mGluR-dependent long-term depression (LTD) formation but enhances NMDAR-dependent long-term potentiation (LTP) production in hippocampal CA1 neurons. The expression levels of postsynaptic proteins, including NR2a, NR1, Shank1 and Shank3, are also altered in Sarm1 knockdown mice, suggesting a role for Sarm1 in that maintenance of synaptic homeostasis. The addition of a positive allosteric modulator of mGluR5, CDPPB, ameliorates the LTD defects in slice recording and the behavioral deficits in social interaction and associative memory. These results suggest an important role for mGluR5 signaling in the function of Sarm1. In conclusion, our study demonstrates a role for Sarm1 in the regulation of synaptic plasticity. Through these mechanisms, Sarm1 knockdown results in the impairment of associative memory and social interactions in mice.